Consumer Buying Intention : Food Choice Preferences Based on Cultural Orientation - Adelia Shifa Samita; Sabiena Amarissa Vianca; Tri Wismiarsi (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This research investigates consumers’ decisions in buying food preferences in regard to cultural orientation, which shall establish how cultural factors reflect consumers’ decisions on food consumption. Culture orientation includes collectivism, long-term orientation, masculinity and uncertainty avoidance by Hofstede. Using a quantitative research approach, the research employed structured questionnaire surveys that help gain overall view from participants of diversified cultural backgrounds. From 107 respondents of an online survey, key findings reveal that there are significant relationships between culture orientation, i.e., long-term orientation and purchase intention. However, two other culture dimensions of Hofstede do not show association with purchase intention. The findings show that long-term orientation, i.e., long-term benefits are very crucial when they decide to buy their food.